2008
DOI: 10.1002/adfm.200700315
|View full text |Cite
|
Sign up to set email alerts
|

Donor–Acceptor C60‐Containing Polyferrocenylsilanes: Synthesis, Characterization, and Applications in Photodiode Devices

Abstract: A series of polyferrocenylsilane (PFS) random copolymers containing covalently bound pendant [C60]fullerene groups, the first well‐characterized metallopolymers with pendant C60 units, have been prepared and characterized. The fullerene content of the prepared copolymers ranges from 7 to 24% relative to monomer unit. The desired copolymers were synthesized in three steps: metal‐catalyzed ring opening polymerization of sila[1]ferrocenophanes was performed to synthesize random copolymers of poly(ferrocenylmethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…0.3 to 0.45 V [95]. Similar responses were obtained when the fullerenes were covalently attached to the polysilane backbone [96]. …”
Section: Solar Energy Materials and Sensorssupporting
confidence: 64%
“…0.3 to 0.45 V [95]. Similar responses were obtained when the fullerenes were covalently attached to the polysilane backbone [96]. …”
Section: Solar Energy Materials and Sensorssupporting
confidence: 64%
“…Among these, metallpolyynes stand out to be particularly interesting candidates in this area [23][24][25][26][27][28][29][30][31][32][33][34][35][36]. For a rational design of solar cells with the aim of optimizing solar spectrum coverage and charge mobility, both in single and tandem cells, it is very desirable to seek for a new class of conjugated polymers with tunable functional properties for PSCs so that they can be processed under similar conditions and the cell design and optimization processes can be simplified [48][49][50][51][52][53][54][55]. It has been shown that organic groups such as fluorene [35], 2,1,3-benzothiadiazole [31,34], thieno [3,4-b]pyrazine [36] and bithiazole [32] can be used to prepare efficient organometallic PSCs with the photosensitivity at longer wavelengths due to their narrow bandgaps.…”
Section: Introductionmentioning
confidence: 99%
“…In the present section, some of the most promising and recent applications for C 60 -polymers will be shown. Since 1991 fullerene polymers have been studied as active materials in membranes both for gas separation [91,92] and for proton exchange fuel cells [93], and also as active polymers in electroluminescent devices [77,94,95] and in non-volatile flash devices [96], among others. One of the most promising applications for polyfullerenes seems to be as an active layer in optical limiters.…”
Section: Properties and Applicationsmentioning
confidence: 99%